Answer:
3 years
Step-by-step explanation:
As with many age problems, you can reason it without equations. If Tom is 13 now, 2 years ago he was 11. If the total age of the two cats at that time was 15, then Tim was 15 -11 = 4.
That means Tim is now 4+2 = 6, so will be 9 in 3 years.
_____
Additional comment
If you want to write equations, there are several ways you can do it. We often like to use variables to represent the current age. We can assign ...
x = Tim's current age; y = Tom's current age.
The sum of their ages 2 years ago was ...
(x -2) +(y -2) = 15
Tom's current age is 13, so we have y=13. Using that in the equation gives ...
x -2 +13 -2 = 15
x = 6 . . . . . . . . . . subtract 9, collect terms
That's Tim's current age, so Tim will be 9 years old in 3 years.